Comparison of ultrasound with computed tomography to measure skeletal muscle mass in critically ill patients: A prospective study protocol. Issue 48 (2nd December 2022) - Peres, Leandro Moreira; Luis-Silva, Fabio; Menegueti, Mayra Gonçalves; Sato, Lucas; Basile-Filho, Anibal; Suen, Vivian Marques Miguel; Martins-Filho, Olindo Assis; Auxiliadora-Martins, Maria
Abstract : Introduction: Therapy and nutritional status directly interfere in the clinical evolution of critically ill patients, in reducing morbidity and mortality, by maintaining the functional integrity of the gastrointestinal tract, decreasing the catabolic response, besides contributing to the reduction of hospitalization time resulting in less treatment cost. Critical patients and trauma victims suffer early changes in the quantity and quality of muscle mass. Tools to identify the groups most susceptible to these complications are necessary so that interventions can minimize the deleterious effects of malnutrition in critically ill patients. Methods and analysis: The aim of the present study is to measure muscle mass loss by measuring the thickness of the rectus femoris muscle by bedside ultrasound in critically ill patients admitted to the Intensive Care Unit (ICU) of a university hospital. Information will be collected regarding the length of hospital and ICU stay, the reason for admission, anthropometric data at admission and during hospitalization, energy needs, nutritional therapy used, and fasting time. This is a prospective, observational study that will be carried out in a single center in an ICU of a tertiary university hospital. The study population will undergo 3 tomographic images and 3 ultrasounds of the rectus femoris of each patient at different times. We propose, unprecedentedly, performing a validation study of ultrasound with the gold standard Computed tomography to evaluate the musculature of critically ill patients victims of traumatic brain injury. The results got will texto be fundamental for the development of new fields of investigation and certainly contribute to the discovery of a new approach to treat sarcopenia in critically ill patients. The Research Ethics Committee approved the study and all patients included will sign an informed consent form. (Clinical Record: RBR-2bzspnz).